“That’s Just the Tip of It Because It Goes Deeper Than That”: A Qualitative Exploration Into the Role of Mental Illness in Offending Onset and Subsequent Offending Behavior - Calhoun, Stacy (Criminal justice policy review, 2018)
There continues to be considerable debate regarding the most effective ways to reduce the number of mentally ill offenders in the adult criminal justice system. What is often missing from this national discussion is an examination of the factors associated with their initial involvement in illegal activities. This qualitative study assesses the self-perceived role that psychiatric symptoms had in the onset and continued offending of a sample of 28 parolees with mental illness. The findings showed that psychiatric symptoms rarely played a direct role in the onset and continued offending in this sample. Furthermore, the majority of the sample started offending prior to the age of 18, highlighting the need to devote more resources toward delivering evidence-based interventions to youth at risk of becoming involved in a criminal lifestyle as one strategy for reducing the number of mentally ill who become involved in the adult criminal justice system.